IMPURITIES AND NONSTOICHIOMETRY IN THE BULK AND ON THE (1014) SURFACE OF DOLOMITE - Wright K.; Cygan R.T.; Slater B. (My University, 2002)
Atomistic computer simulation methods have been used to model the nature of nonstoichiometry and impurity defects in the bulk and at the (1014) surface of dolomite (MgCa(CO3)2). Calcium and Mg in the bulk and at the surface have been replaced with divalent Ni, Co, Zn, Fe, Mn, and Cd. The results of these calculations indicate that in the bulk, these impurities will prefer to substitute at the Ca site rather than the Mg site. Ca excess in dolomite is most likely incorporated as basal stacking faults; this nonstoichiometry can influence the site distribution of impurities. The calculated surface segregation energies suggest that of all the impurities studied, only Cd will show a strong preference for the (1014) surface of dolomite.